Policy Value of Basic Law in The Process of Criminal Investigation by Polri Investigator - Kholid Mawardi; Anis Mashdurohatun (Jurnal Daulat Hukum, 2018)
Policy value of basic law of investigation on the handling of an offense by the police investigators is still less than the maximum because public distrust and dissatisfaction factors on the performance of the Police. The purpose of this research isto describe rate policy the basic law, the factors that influence and examine how the investigation should be done on the handling of criminal assault by police investigators in the present and future. The method used in this research is the approach normatife juridical and empirical approaches. Type of research is descriptive. Primary data and secondary data is data used in this study. Methods of data collection in this study using observation, interview and literature study. Analysis of data using qualitative descriptive method. The study states that 1) in order to hold the inquiry and investigation, the Investigation Police Investigation Unit and has implemented procedures in accordance with the prescribed rules legislation; 2) The most dominant factor affect the investigation that is a factor of society 3) The efforts made in overcoming the barriers that exist, such as by holding socialization and explain the importance of the role of investigator in handling criminal offense.Keywords: Basic Law; Investigation; Investigator.